2015
DOI: 10.4038/sljpsyc.v6i1.8056
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Stress Sensation Inventory (SSI) to measure stress among students aged 15 to 19 years in Sri Lanka

Abstract: Background Despite the fact that stress may be associated with adverse psychological effects, there are no validated scales to measure stress among Sri Lankan adolescents. Objectives To develop and validate a scale (SSI) to measure stress among students aged 15 to 19 years in Sri Lanka. Methods In-depth interviews and focus group discussions were conducted among adolescents, in order to explore physical symptoms and thoughts experienced and their behavioural responses, when faced with challenging problems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The quantitative component of sleep mainly comprises of duration, while the qualitative aspect includes depth of sleep and restfulness upon awakening (2). Prior work has suggested that university students have poor sleep habits and sleeping patterns such as insubstantial sleep, irregular bedtimes on weekdays and weekends as reasons for their poor sleep quality (4). Research from Finland found that frequent waking up during the night is complained of mainly by female students (5).…”
mentioning
confidence: 99%
“…The quantitative component of sleep mainly comprises of duration, while the qualitative aspect includes depth of sleep and restfulness upon awakening (2). Prior work has suggested that university students have poor sleep habits and sleeping patterns such as insubstantial sleep, irregular bedtimes on weekdays and weekends as reasons for their poor sleep quality (4). Research from Finland found that frequent waking up during the night is complained of mainly by female students (5).…”
mentioning
confidence: 99%
“…[2] Commonly stated causes the students with poor sleep quality have described the reasons for their poor sleep quality as poor sleep habits and patterns like insubstantial sleep, irregular bedtimes on weekdays and weekends. [4]. A research carried out in Finland revealed that more frequent waking up during the night is complained mainly by female students.…”
mentioning
confidence: 99%
“…When considering the available local statistics, a study to evaluate stress among school-going adolescents aged 15-19 years in Gampaha district showed 47.2% prevalence of stress and higher prevalence was identified among males than females. 2 There are a lot of educational, social, physical and emotional stressors that these students have to face during this period. The demand for educational achievements, high parental expectations, family factors and romantic relationships build up a stressful environment towards the student.…”
mentioning
confidence: 99%